Pengaruh Model Investigasi Kelompok terhadap Hasil Belajar Siswa pada Mata Pelajaran Sejarah Indonesia - Rina Eryuliana; Wahidul Basri; Aisiah Aisiah (PAKAR Pendidikan, 2019)
This study aims to look at the effect of the Group Investigation model on students’ learning outcomes in the subject of Indonesian History to students in class XI IPS in SMAN 5 Padang in the ability to understand causality in historical events. This type of research is quantitative with the experimental method. Data obtained from the learning outcomes of students of class XI IPS SMAN 5 Padang. The study population consisted of 3 classes, the selection of samples was taken based on cluster sampling. The hypothesis proposed was there is an influence of students’ learning outcomes by using the Group Investigation model on students' abilities about understanding cause-effect in historical events. The data analysis technique is done by normality test, homogeneity test, and hypothesis testing. The results showed that there was an influence of the Group Investigation model on students’ learning outcomes in Indonesian History subjects in class XI IPS at SMAN 5 Padang. After pretest and posttest, there were differences in mean values. The average value of the experimental class pretest was 6.62 and the control class was 4,074. The average value of the experimental class posttest was 7,629 and the control class was 5,074. Analysis of the normality test showed that the two samples were normally distributed, namely Lhit <L. tab, experimental class was 0.786 and control class was 0.819 with L. tab was 0.886. The sample homogeneity test results have a homogeneous variant, namely F.hit 1.3 <1.7. The results of the t test show Thit> Ttab which is 6.8166> 2.0555 so that H1 can be stated and H0 is rejected. Based on the results of the study that there is an influence of the Group Investigation model on students’ learning outcomes in Indonesian History subjects in class XI IPS SMAN 5 Padang.